2019
DOI: 10.1002/anie.201812472
|View full text |Cite
|
Sign up to set email alerts
|

There and Back Again—The Journey of LiNiO2 as a Cathode Active Material

Abstract: This Review provides a comprehensive overview of LiNiO2 (LNO), almost 30 years after its introduction as a cathode active material. We aim to highlight the physicochemical peculiarities that make LNO a complex material in every aspect. We specifically stress the effect of the Li off‐stoichiometry (Li1−zNi1+zO2) on every property of LNO, especially the electrochemical ones. The key instability issues that plague the compound and the strategies that have been implemented so far to overcome them are discussed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
565
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 507 publications
(609 citation statements)
references
References 265 publications
17
565
2
3
Order By: Relevance
“…The a lattice parameter in both NCM111 and NCM811 CAMs gradually decreases in a similar manner (Figure 3a). [140] Li et al [139] recently presented results from operando XRD on LNO. Even more pronounced composition-dependent differences are seen in the behavior of the c-axis.…”
Section: Crystallographic Changes In Ncmmentioning
confidence: 99%
See 1 more Smart Citation
“…The a lattice parameter in both NCM111 and NCM811 CAMs gradually decreases in a similar manner (Figure 3a). [140] Li et al [139] recently presented results from operando XRD on LNO. Even more pronounced composition-dependent differences are seen in the behavior of the c-axis.…”
Section: Crystallographic Changes In Ncmmentioning
confidence: 99%
“…[26,27,106,[137][138][139] A detailed description and visualization of the LNO structure is provided in a recent review article. [140] Li et al [139] recently presented results from operando XRD on LNO. Here, the crystallographic changes are so distinct that the appearance of individual Li x NiO 2 phases can be readily tracked.…”
Section: Crystallographic Changes In Ncmmentioning
confidence: 99%
“…Figure 3a depicts the contour plots of several XRD peaks-(003), (101), (108), and (110) at the first charging process. [4,15,16] Figure 3b gives more detailed information on the a-lattice parameter change as a function of voltage. Energy Mater.…”
Section: Structural Analysismentioning
confidence: 99%
“…LNO can delivers pecific chargec apacities > 240 mAh g À1 at 4.3 Vv ersusL i + /Li. However,d ue to increasing demands in energy density,inp articularf or electric vehicles, in recent years the cathode chemistry is more and more pushed back to Nirich compositions (> 80 %N i).T hisd evelopment inspired both academia and industry to revisit LNO, [9] mainly aiminga te xploring the upper limit of Ni content in layered oxide CAMs. [5] Improved first-cyclee fficiencies have been achieved for LNO synthesized using excess Li, [6][7][8] but numerous other issues also affect the cycling performance negatively.A fter severaly ears of intense research, structurala nd chemical instabilities have been identified as most criticali ssues hindering commercialization of LNO,a nd battery developerss tarted to partially substitute Ni by other metals( Mn, Co, Al), bringing NCA (Li[Ni 1ÀxÀy Co x Al y ]O 2 )a nd NCM (Li 1 + z [Ni 1ÀxÀy Co x Mn y ] 1Àz O 2 )C AMsi nto the market.…”
Section: Introductionmentioning
confidence: 99%
“…Such solidsolution CAMs strongly benefitf rom synergetic effects of the different metals. However,d ue to increasing demands in energy density,inp articularf or electric vehicles, in recent years the cathode chemistry is more and more pushed back to Nirich compositions (> 80 %N i).T hisd evelopment inspired both academia and industry to revisit LNO, [9] mainly aiminga te xploring the upper limit of Ni content in layered oxide CAMs. [10] Several issues, mainly related to instabilities, are responsible for the failure of LNO cells in the past.…”
Section: Introductionmentioning
confidence: 99%